Transaxillary Intra-Aortic Balloon Pump Migration Minimized With a Long Introducer Sheath - Dorsey, Andrew; Karimianpour, Ahmadreza; Fernandes, Valerian L. (Cardiovascular revascularization medicine, 2021)
Intra-aortic balloon pump (IABP) has been used more recently as a bridge to cardiac transplantation in hospitalized patients. Femoral IABP limits mobility and rehabilitation; thus, transaxillary approach has been described. However, a transaxillary IABP may migrate, causing significant vascular injury, potential death, or disqualification from transplantation. We describe a case of a 67-year-old male with transaxillary IABP inserted to allow for pre-transplant physical rehabilitation. Due to the unfolded nature of his aorta, the IABP coiled onto itself and migrated several times. We employed a novel technique to mitigate IABP migration using a long 25-cm introducer sheath. •Transaxillary intra-aortic balloon pumps are prone to migration.•Intra-aortic balloon pump migration leads to serious vascular complications.•A long introducer sheath can help minimize device migration.